ANALISIS KINERJA BERBASIS KONFLIK DAN BEBAN KERJA STUDI PADA KARYAWAN SIDIQ MANAJEMEN YOGYAKARTA - Agung Nugroho (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2021)
There are a number of factors influencing work performance, some are work conflict, work burden, and work stress. The purpose of this research is to know how influence of work conflict and work burden to employees’ work performance, using intervening variable of work stress on employees of Sidiq Manajemen Yogyakarta. The data collecting method used questionnaire and the sample collecting used census by giving questionnaire to all of the employees in all culinary business unit of Sidiq Manajemen Yogyakarta as many as 44 respondents. The data was analyzed by pathway analysis using SPSS 18.0 and SmartPLS 3.2.8.   This research shows that work conflict has positive and significant influence to work stress, work burden has positive influence but it is not significant to work performance, work stress has no influence and it is not significant to work performance, and work stress has positive influence but it is not significant to work performance on employess of Sidiq Manajemen Yogyakarta. Keyword: conflict, burden, stress, work performance